Autoimmune Coagulation Factor X Deficiency as a Rare Acquired Hemorrhagic Disorder: A Literature Review - Ichinose, Akitada; Osaki, Tsukasa; Souri, Masayoshi (Thrombosis and Haemostasis, 2021)
Coagulation factor X (F10) amplifies the clotting reaction in the middle of the coagulation cascade, and thus F10 deficiency leads to a bleeding tendency. Isolated acquired F10 deficiency is widely recognized in patients with immunoglobulin light-chain amyloidosis or plasma cell dyscrasias. However, its occurrence as an autoimmune disorder is extremely rare. The Japanese Collaborative Research Group has been conducting a nationwide survey on autoimmune coagulation factor deficiencies (AiCFDs) starting in the last decade; we recently identified three patients with autoimmune F10 deficiency (AiF10D). Furthermore, an extensive literature search was performed, confirming 26 AiF10D and 28 possible cases. Our study revealed that AiF10D patients were younger than patients with other AiCFDs; AiF10D patients included children and were predominantly male. AiF10D was confirmed as a severe type of bleeding diathesis, although its mortality rate was not high. As AiF10D patients showed only low F10 inhibitor titers, they were considered to have nonneutralizing anti-F10 autoantibodies rather than their neutralizing counterparts. Accordingly, immunological anti-F10 antibody detection is highly recommended. Hemostatic and immunosuppressive therapies may help arrest bleeding and eliminate anti-F10 antibodies, leading to a high recovery rate. However, further investigation is necessary to understand the basic characteristics and proper management of AiF10D owing to the limited number of patients.
Keywords: coagulation; factor X; bleeding disorders; autoantibodies; nonneutralizing